2019
DOI: 10.33160/yam.2019.03.017
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Combined Tumor Marker and Controlling Nutritional Status (CONUT) Score in Colorectal Cancer Patients

Abstract: Background Nutritional status is strongly associated with prognosis in cancer patients. Controlling Nutritional Status (CONUT) score is a nutritional marker based on serum albumin, cholesterol, and total lymphocyte count. We investigated the prognostic significance of a combination of the tumor marker carcinoembryonic antigen (CEA) and CONUT score (T-CONUT) in colorectal cancer (CRC) patients. Methods A total of 522 patients who underwent surgery for CRC at our hospital were retrospectively enrolled in this st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 32 publications
1
18
0
1
Order By: Relevance
“…A systematic search of the literature resulted in 247 abstracts. After screening the abstracts, 9 full-text manuscripts were assessed for eligibility and included in the present study [9][10][11][14][15][16][17][18][19], as represented in Table 1. All included studies were single-center retrospective series.…”
Section: Resultsmentioning
confidence: 99%
“…A systematic search of the literature resulted in 247 abstracts. After screening the abstracts, 9 full-text manuscripts were assessed for eligibility and included in the present study [9][10][11][14][15][16][17][18][19], as represented in Table 1. All included studies were single-center retrospective series.…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, many studies have reported the CONUT score to be a novel predictive index for the prognosis of malignant tumors. It has been shown to be associated with the prognosis of patients with gastric cancer, colorectal cancer, lung cancer, liver cancer, and clear cell renal cell carcinoma 9–13. However, the clinical value of the CONUT score in epithelial ovarian cancer has not been evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…A variety of laboratory biomarkers have been developed that use the systemic inflammation or nutritonal status of patients as a simple tool. These biomarkers have been demonstrated to predict the prognosis in various cancers, and several studies have demonstrated that these indicators are predictive of the prognosis of patients with CRC 2,7,8 . However, to the best of our knowledge, there is no report on which prognostic indicators are the most useful for CRC patients after curative surgery.…”
mentioning
confidence: 99%